Stochastic Optimization Model for Detailed Long-term Hydro Thermal Scheduling Using Scenario-tree Simulation. (January 2016) - Warland, Geir; Mo, Birger
Abstract: The paper presents a case study comparing two models for hydro-thermal scheduling. Both models are tools that can be applied for forecasting and planning in electricity markets, taking into account inter-connected power markets and using detailed hydro modelling. The first model, which is used as the reference, is in operative use by most market players in the Nordic power market. The second model is a new prototype which is expected to give better utilization in systems with large shares of hydro power because it to a larger extent is based on formal optimization. The case study compares the models with regard to differences in hydropower scheduling, market prices and socio-economic surplus.